UNUSUAL FOREIGN BODY INGESTION LEADING TO BOWEL OBSTRUCTION - Dr. Khalid Usman; Dr. Muhammad Moazzam Farooq; Dr. Aamir Ahmed; Dr. Ameer Hamza; Dr. Zubair Ahmad; Dr. Ammar Munawar; Dr. Muhammad Tayyab Khan; Dr. Moosa Ali; Dr. Samandar Khan Babar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Herein, we report a case of a 62-year-old man with underlying diabetes and hypertension who presented to our hospital with symptoms including severe abdominal pain, vomiting associated with obstipation (failure in bowel motion), and confusion. Referred from Talash Dir Lower Pakistan, the clinical appearance was of a patient whose symptoms had worsened over 48 hours. The history of the present illness was followed by a physical examination and laboratory tests, which were consistent with a bowel obstruction. Diagnostic imaging confirmed an ileal obstruction due to a foreign body. A laparotomy was performed, and the foreign body was successfully removed. Immediately after hospital discharge, the patient was asymptomatic with no complications involving centralized postoperative recovery. Conclusion This case would bring to the forefront thinking outside of the zone in terms of diagnosis approach, including rare foreign body ingestion on the differential for bowel obstruction abdomen, especially with no apparent history.